Essential Teaching Instructions for Teachers in Language Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Reading is an activity with a purpose. A person may read in order to gain information or verify existing knowledge, or in order to critique a writer‘s ideas or writing style. A person may also read for enjoyment, or to enhance knowledge of the language being read. The purpose for reading also determines the appropriate approach to reading comprehension. The communicative approach to language teaching has given instructors a different understanding of the role of reading in the language classroom and the type of texts that can be used in instruction.